Uptake and impact of Climate Smart Agriculture on food security, incomes and assets in East Africa - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
Adoption is examined across multiple location - Kenya, Uganda and Tanzania, and impact assessment uses Nyando in Western Kenya as the case study.